ANALISIS STRATEGI PERLUASAN RUTE BUS RAPID TRANSPORT BRT TRANS JATENG KORIDOR 6 SEMARANGGROBOGANBLORA - Ristiyanto, Hartono Guntur; Jatmiko, Suluh; Marahendra, Wawan Dedi; Nafiah, Khitthatun (Universitas PGRI Semarang, 2026)
The number of passenger trips from Grobogan to Blora is the 1st largest passenger trip and vice versa from Blora to Grobogan is the 2nd largest compared to the number of trips from Grobogan to other regencies/cities in Central Java and vice versa. Fulfillment of the community's need for decent public transportation, such as Bus Rapid Transport (BRT), is needed to accommodate the potential number of passengers. The expansion of BRT services requires an initial analysis of what factors support and do not support the expansion and what strategies should be formulated for the purposes of the expansion. The collection of research data used the interview method via google form. Respondents were selected using the purposive sampling method. While data analysis used the SWOT (Strengths, Weaknesses, Opportunities, Threats) method and IFAS (Internal Strategic Factors Analysis) and EFAS (External Strategic Factors Analysis) analysis. The results of the analysis concluded that there were 14 factors that supported and 9 factors that did not support the expansion of BRT route services. Based on the SWOT analysis, there are 3 main factors that support route expansion, namely: availability of infrastructure, opportunities for cooperation with various parties, and public enthusiasm. While factors that do not support: route expansion has not been included in the development plan and there are differences in agglomeration. Meanwhile, the results of the calculation of the IFAS and EFAS values obtained the results of the IFAS score = 1.24 and EFAS = 0.48. By using these two values as the abscissa and ordinate axis values, the coordinates in quadrant I are obtained. The appropriate strategy in quadrant I is a progressive strategy by utilizing existing strengths to achieve opportunities.